University of Maribor, Faculty of Civil Engineering, Transportation Engineering and Architecture (University of Maribor Press, 2018)
The book presents promotional material of the Faculty of Civil Engineering, Transportation Engineering and Architecture of the University of Maribor. It starts with the dean’s words, the vision of the faculty, and continues with its history. All activities of faculty are shown from the descriptions of the implementation of study programs at all three levels, to scientific and research activities and development and professional work.